Review: Phytochemical Screening, Secondary Metabolites and Biological Activities of Southeast Sulawesi Plants - Megawati Megawati (Hasanuddin University, 2020)
Southeast Sulawesi is one of the provinces in Indonesia which has a variety of medicinal plants that have been used by its people in treating diseases. The results of research on phytochemical screening and isolation of secondary metabolites from local researchers indicated that the plants from Southeast Sulawesi have the potential to be studied further. Plants from Southeast Sulawesi show pharmacological potential activities that can be developed for the purpose of treating diseases caused by bacteria, fungi, cancer, and as an antioxidants. There are Southeast Sulawesi endemic plants from the Etlingera genus that are interesting to explore (phytochemical screening, isolation of pure compounds and pharmacological studies) considering that of the 14 species of Etlingera plants scattered in Southeast Sulawesi, 2 (two) of which have recently been reported, namely E. elatior and E. calophrys